The detrimental effects of progression of retinal degeneration in the visual cortex - Bhattacharyya, Anwesha (Frontiers in Cellular Neuroscience, 2022)
The leading cause of blindness in inherited and age-related retinal degeneration (RD) is the death of retinal photoreceptors such as rods and cones. The most prevalent form of RD is age-related macular degeneration (AMD) which affects the macula resulting in an irreversible loss of vision. The other is a heterogenous group of inherited disorders known as Retinitis Pigmentosa (RP) caused by the progressive loss of photoreceptors. Several approaches have been developed in recent years to artificially stimulate the remaining retinal neurons using optogenetics, retinal prostheses, and chemical photoswitches. However, the outcome of these strategies has been limited. The success of these treatments relies on the morphology, physiology, and proper functioning of the remaining intact structures in the downstream visual pathway. It is not completely understood what all alterations occur in the visual cortex during RD. In this review, I will discuss the known information in the literature about morphological and functional changes that occur in the visual cortex in rodents and humans during RD. The aim is to highlight the changes in the visual cortex that will be helpful for developing tools and strategies directed toward the restoration of high-resolution vision in patients with visual impairment.